TRACKING AND REFERRAL BY NURSES IN THE FAMILY HEALTH STRATEGY OF VIOLENCE CASES AGAINST WOMEN - Josy Cárolen Vieira de Lima; Renata Clemente dos Santos; Jessyka Chaves da Silva; Rebeca de Sousa Costa da Silva; Cláudia Maria Ramos Medeiros Souto; Rafaella Queiroga Souto; Gleicy Karine Nascimento de Araújo (Universidade Federal do Paraná, 2020)
Objective: understand how the tracking and referral of cases of violence against women by nurses of the Family Health Strategy of the upstate Paraíba are carried out. Method: a transversal, qualitative study, with the participation of seven nurses working in the Family Health Strategy, linked to the VI health district of the municipality of Campina Grande, Paraíba. The collection took place in September 2018 and a content analysis of Bardin was performed. Results: three categories have emerged: I - Concepts of violence (29.3%); II - Tracking of violence cases (53.7%); III - Referral of violence cases (17.1%). The words "physical aggression", "woman's police station", "social worker", "psychological", "denounce", "remember", "suffer", "physical" were observed. Conclusion: nurses understand violence and the gynecological consultation serves to identify cases. The research clarifies points of the fragility of health services that make it difficult to fight violence and demonstrate the need for team qualification.